PERAN SELF-EFFICACY DAN SIKAP KEUANGAN SEBAGAI VARIABEL MEDIASI PADA PENGARUH PENGETAHUAN KEUANGAN TERHADAP PERILAKU KEUANGAN - Agitya Rindivenessia; Muhammad Ali Fikri (Universitas Muhammadiyah Metro Lampung, 2021)
The purpose of this study was to determine the role of financial attitudes and self-efficacy as a mediating variable on the effect of financial knowledge on financial behavior. The population of this study was 1,089 respondents consisting of Lecturers at the Faculty of Economics and Business and Lecturers of Islamic Banking in Indonesia, namely Yogyakarta, Palembang, Lampung, and Tulung Agung. The sample in this study was selected using purposive sampling method of 99 respondents. The data processing technique used in this research is the structural equation modeling technique using the Smart-PLS 3.0 application. The results of this study: First, high financial knowledge will influence good financial behavior. Second, high financial knowledge will influence good financial behavior with financial attitudes as a mediating variable. Third, high financial knowledge will influence good financial behavior with self-efficacy as a mediating variable. Keywords: Financial Knowledge; Financial Attitude; Self-Efficacy; Financial Behavior